Ni nanoparticles/V₄C₃Tₓ MXene heterostructures for electrocatalytic nitrogen fixation - Du, Cheng-Feng (2022)
Electrocatalytic nitrogen reduction reaction (NRR) to generate ammonium is a promising renewable technology for nitrogen cycling. Engineering the composition and surface states of an electrocatalyst is critical to improve the intrinsic NRR performance. Here, a facile preparation of Ni nanoparticles (NPs) loaded on V4C3Tx MXene (denoted as Ni@MX) as a highly efficient NRR electrocatalyst is reported. Remarkably, the Ni@MX nanocomposite presents an ammonia yield rate of 21.29 mu g h(-1) mg(cat)(-1) at 0.2 mA cm(-2). The presented NRR activity is considerably higher than that of the recently reported MXene derivatives and is even comparable to that of the noble-metal-based electrocatalysts. Combined with various characterization methods and the density functional theory (DFT) simulation, we propose that the improved NRR activity was ascribed to a synergistic NRR route by Ni sites in the nanoparticles and the surface O vacancy of V4C3Tx MXene. Given the remarkable improvement of NRR activity on the MXene-based nanocomposites, this work demonstrates the critical role of MXene and its derivatives with surface modification as electrocatalysts.